An amino acid fertilizer improves the emergent accumulator plant Nasturtium officinale R. Br. phytoremediation capability for cadmium-contaminated paddy soils - Zhang, Ran; Liu, Qin; Xu, Xiangting; Liao, Ming’an; Lin, Lijin; Hu, Rongping; Luo, Xian; Wang, Zhihui; Wang, Jin; Deng, Qunxian; Liang, Dong; Xia, Hui; et al. (Frontiers in Plant Science, 2022)
Cadmium (Cd) contamination of paddy soil affects safe crop production. This study aimed to evaluate the effects of plant biostimulant amino acid fertilizer on the phytoremediation capability of an emergent accumulator plant Nasturtium officinale R. Br. for Cd-contaminated paddy soils. A pot study was carried out to study the effects of different concentrations of amino acid fertilizer on the Cd accumulation of N. officinale grown in Cd-contaminated paddy soil. The amino acid fertilizer increased the biomass of N. officinale. The amino acid fertilizer concentration exhibited a quadratic polynomial regression relationship with the root and shoot biomass. The fertilizer also increased the photosynthetic pigment (chlorophyll and carotenoid) contents, peroxidase (POD; EC 1.11.1.7) activity, and catalase (CAT; EC 1.11.1.6) activity of N. officinale, but decreased the soluble protein content and had no significant effect on the superoxide dismutase (SOD; EC 1.15.1.1) activity. Furthermore, the amino acid fertilizer increased the Cd content and Cd extraction of N. officinale. The shoot Cd extraction increased by 29.06%, 63.05%, 77.22%, and 17.40% at 1500-, 1200-, 900-, and 600-fold dilutions of the amino acid fertilizer, respectively, compared with the control. Moreover, the amino acid fertilizer promoted the Cd transport from the roots to shoots of N. officinale. The amino acid fertilizer concentration also exhibited a quadratic polynomial regression relationship with the root Cd content, shoot Cd content, root Cd extraction, and shoot Cd extraction, respectively. The correlation, grey relational, and path analyses revealed that the root biomass, shoot biomass, chlorophyll content, catalase activity, shoot Cd content, and root Cd extraction were closely associated with the shoot Cd extraction. Therefore, the amino acid fertilizer can promote Cd uptake and improve the phytoremediation capability of N. officinale to remediate Cd-contaminated paddy soils, and 900-fold dilution is the most suitable concentration.